Some Generalized Difference Cesàro Double Sequence Space of Fuzzy Real Number Defined by Double Orlicz Function (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
In this paper we introduce some generalized difference Cesàro double sequence space of fuzzy real number by using double orlicz function . and we study their different properties like completeness , solidity, symmwtricity etc. . Also we obtain some inclusion relation involving these double sequence space.